2010
DOI: 10.3844/ajbbsp.2010.19.24
|View full text |Cite
|
Sign up to set email alerts
|

Do Resistin and Tumor Necrosis Factor-α Relate to Changes in Insulin Resistance in Normal Pregnancy?

Abstract: Problem statement:The purpose of this study was to evaluate the role of resistin and Tumor Necrosis Factor-α (TNF-α) in insulin resistance during pregnancy. Approach: Serum resistin and TNF-α concentrations were measured by ELISA in 86 healthy pregnant women (26, 23 and 37 of them in the 1st, 2nd and 3rd trimesters, respectively) and in 21 healthy non pregnant women in a cross sectional study. Results: Resistin concentration was significantly higher in the third trimester (9.5±3.3 ng mL −1 ) as compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Statistical analysis: Data were presented as mean ± Standard Error of Mean (SEM) (Adeyemi, 2009;Zareian et al, 2010). One-way Analysis Of Variance (ANOVA) (Parsakhoo et al, 2009;Zareian et al, 2010;Iqbal and Khan, 2010;Hashemi, 2010), followed by Duncan's test.…”
Section: Stereotypy Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis: Data were presented as mean ± Standard Error of Mean (SEM) (Adeyemi, 2009;Zareian et al, 2010). One-way Analysis Of Variance (ANOVA) (Parsakhoo et al, 2009;Zareian et al, 2010;Iqbal and Khan, 2010;Hashemi, 2010), followed by Duncan's test.…”
Section: Stereotypy Behaviorsmentioning
confidence: 99%
“…One-way Analysis Of Variance (ANOVA) (Parsakhoo et al, 2009;Zareian et al, 2010;Iqbal and Khan, 2010;Hashemi, 2010), followed by Duncan's test. A probability level less than 0.05 were accepted as significance.…”
Section: Stereotypy Behaviorsmentioning
confidence: 99%
“…In a recently published study, it has been reported that in normal pregnant women both maternal IL-6 (Jahromi et al, 2011a) and TNF-α cytokines are increased (Zareian et al, 2010;Elsamanoudy and Abbas, 2010) and IL-1β is decreased (Jahromi et al, 2011b), But it was not find any correlation between IR with IL-6 and TNF-α. (Jahromi et al, 2011a) and between IR with IL-1β (Jahromi et al, 2011b).…”
Section: Introductionmentioning
confidence: 87%
“…Calculation of insulin sensitivity indexes HOMA-IR index was calculated as an estimate of insulin sensitivity. It was calculated, analogous to the assumptions applied in the development of HOMA-IR in humans (Matthews et al, 1985), using the following equation: HOMA-IR = (FPG X FSI)/2.430 (Cacho et al, 2008;Zareian et al, 2010).…”
Section: Placental Tissue Homogenate Preparationmentioning
confidence: 99%